2013
DOI: 10.1088/0143-0807/34/2/225
|View full text |Cite
|
Sign up to set email alerts
|

Small amplitude transverse waves on taut strings: exploring the significant effects of longitudinal motion on wave energy location and propagation

Abstract: Introductory discussions of energy transport due to transverse waves on taut strings universally assume that the effects of longitudinal motion can be neglected, but this assumption is not even approximately valid unless the string is idealized to have a zero relaxed length, a requirement approximately met by the slinky spring. While making this additional idealization is probably the best approach to take when discussing waves on strings at the introductory level, for intermediate to advanced undergraduate cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…Butikov [18] criticized these conclusions, but also stated that the potential energy of the string resulted from the elastic stretching (ELONG argument). Rowland [19] concluded that Morse and Feshbach were correct, stating that the potential energy of deformation defined using the curvature was non-unique, and on that basis rejected the energy density defined using curvature (the CURV argument); the more fundamental problem with rigid body translation was not realized in [19] though.…”
Section: Discussionmentioning
confidence: 99%
“…Butikov [18] criticized these conclusions, but also stated that the potential energy of the string resulted from the elastic stretching (ELONG argument). Rowland [19] concluded that Morse and Feshbach were correct, stating that the potential energy of deformation defined using the curvature was non-unique, and on that basis rejected the energy density defined using curvature (the CURV argument); the more fundamental problem with rigid body translation was not realized in [19] though.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding flow is The potential energy density (7c) has been obtained before using a force times distance argument of an infinitesimal string segment evaluated for a continuous quasistatic transition of the string [4, 8, p. 126]. However, only recently a continuity equation of the form (6) has been stated [9]. In order to elucidate the contributions to the flow, write the wave velocity in the restricted case of a positive direction traveling wave…”
Section: Complementary Fields Conservation Equationmentioning
confidence: 99%
“…The longitudinal displacement of the segments has been neglected in this simple model. The relevance of the longitudinal coupling in more realistic models has been addressed by different authors [1,9,22]. Here, the problem is restricted solely to the gradient in the y transverse direction, F y = −(∇V ) y = − y V .…”
Section: Force Derived From % Pot Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it can be seen that x¢ is of the same order of magnitude as ¢ ( )y 1 2 2 , and so longitudinal displacements play a non-negligible role in determining the local tension in a vibrating string (see also [3]). Note that this conclusion is true regardless of whether the string is vibrating 1 This analysis reveals a problem with using the notation commonly used to describe linear transverse vibrations in a string when one is analysing nonlinear motion: the position of a point in a string is not given by ( ( ) ( ) x y x t z x t , , , , as is a reasonable approximation in a linear analysis, but by…”
Section: On the 3/2 Discrepancy In The Nonlinear Coefficientmentioning
confidence: 99%